Sharing and hiding religious knowledge in early Judaism, Christianity, and Islam - Popović, Mladen; Roig Lanzillotta, Lautaro; Wilde, Clare Elena (Judaism, Christianity, and Islam - tension, transmission, transformation, 2018)
Few studies focus on the modes of knowledge transmission (or concealment), or the trends of continuity or change from the Ancient to the Late Antique worlds. In Antiquity, knowledge was cherished as a scarce good, cultivated through the close teacher-student relationship and often preserved in the closed circle of the initated. From Assyrian and Babylonian cuneiform texts to a Shi'ite Islamic tradition, this volume explores how and why knowledge was shared or concealed by diverse communities in a range of Ancient and Late Antique cultural contexts. From caves by the Dead Sea to Alexandria, both normative and heterodox approaches to knowledge in Jewish, Christian and Muslim communities are explored. Biblical and qur'anic passages, as well as gnostic, rabbinic and esoteric Islamic approaches are discussed. In this volume, a range of scholars from Assyrian studies to Jewish, Christian and Islamic studies examine diverse approaches to, and modes of, knowledge transmission and concealment, shedding new light on both the interconnectedness, as well as the unique aspects, of the monotheistic faiths, and their relationship to the ancient civilisations of the Fertile Crescent.